186k views
4 votes
Factor completely the polynomial:ax–y+x–ay

1 Answer

4 votes

Answer:

The factors for the given polynomial is (x-y) and (a+1)

Therefore
ax-y+x-ay=(x-y)(a+1)

Explanation:

Given polynomial expression is
ax-y+x-ay

To simplify the given polynomial:


ax-y+x-ay


=ax+x-ay-y ( Rewritting the above polynomial)


=(a+1)x-(a+1)y (Taking the common terms )


=x(a+1)-y(a+1)(using commutative property )


=(x-y)(a+1) (taking common factor )

Therefore
ax-y+x-ay=(x-y)(a+1)

Therefore the factors for the given polynomial is (x-y) and (a+1)

User Jay Jay Jay
by
4.7k points